EFFECTS OF A PROFESSIONAL DEVELOPMENT PROGRAM ON BEHAVIORAL ENGAGEMENT OF STUDENTS IN MIDDLE AND HIGH SCHOOL. Issue 2 (12th November 2013) - Gregory, Anne; Allen, Joseph P.; Mikami, Amori Y.; Hafen, Christopher A.; Pianta, Robert C.
<x xml:space="preserve">Abstract</x> Student behavioral engagement is a key condition supporting academic achievement, yet student disengagement in middle and high schools is all too common. The current study used a randomized controlled design to test the efficacy of the My Teaching Partner‐Secondary program to increase behavioral engagement. The program offers teachers personalized coaching and systematic feedback on teachers' interactions with students, based on systematic observation of videorecordings of teacher‐student interactions in the classroom. The study found that intervention teachers had significantly higher increases, albeit to a modest degree, in student behavioral engagement in their classrooms after 1 year of involvement with the program compared to the teachers in the control group (explaining 4% of variance). In exploratory analyses, two dimensions of teachers' interactions with students—their focus on analysis and problem solving during instruction and their use of diverse instructional learning formats—acted as mediators of increased student engagement. The findings offer implications for new directions in teacher professional development and for understanding the classroom as a setting for adolescent development.